Sustainable Nonwoven Triboelectric Nanogenerator Including Pseudo‐Thickness Enabled Consistent Power Generation in Ultralow Contact Frequency - Joo Hyung Lee; Jihee Lee; Seongjae Oh; Younghwan Bae; Yoonsu Lee; Hyeon Jun Sim; Guhjoo Ahn; Shi Hyeong Kim; Taehwan Lim (Small Structures, 2025)
A poly(ethylene terephthalate) (PET) nonwoven‐fabric‐based triboelectric nanogenerator (NWF‐TENG) with high energy‐harvesting efficiency at ultralow contact frequencies is introduced, enabled by the concept of pseudo‐thickness. PET‐based NWF exhibits consistent mechanical properties regardless of its origin, even including recycled PET sources, providing the sustainable benefits of the NWF‐TENG system. Above all, this study is the first demonstration to analyze the impact of thickness changes in compressible dielectric materials within dielectric‐to‐dielectric contact TENG models. Through RC decay analysis, it is revealed that the peak‐to‐peak voltage of compressible NWF‐PET is 2,653 V, significantly higher than that of conventional noncompressible film‐based TENG (F‐TENG). After combining with a power management system, the compressible NWF‐TENG achieves a continuous direct current output of 24.8 mW m−2, indicating its potential for powering electronic devices. Lastly, the NWF‐TENG exhibits outstanding charge preservation capability at ultralow contact frequencies due to its sustained contact state during compression cycles of the dielectric NWF material. In an application test, a stopwatch is continuously powered by a 0.0025 m2 NWF‐TENG operating at a contact frequency of 0.2 Hz. In this work, valuable insights are provided into the design and optimization of the energy harvesting systems using compressing materials with the valid pseudo‐thickness concept.